REACTIVE TRHOMBOCYTOSIS IN CHILDREN - Ayu Hafsari; Nadirah Rasyid Ridha (International Journal of Health Science & Medical Research, 2022)
Thrombocytosis is a condition which the platelet count exceeds 450,000/mm3. Thrombocytosis was classified as: mild (450,000-700,000/mm3), moderate (700,000-900,000/mm3), severe (900,000-1,000,000/mm3) and extreme (1,000,000/mm3). Functionally, thrombocytosis is divided into primary (essential) and secondary (reactive). The novelty of this study due to examining reactive thrombocytosis in children. The purpose of this study was to look at reactive thrombocytosis in children.  Essential thrombocytosis is a myeloproliferative disorder due to monoclonal or polyclonal abnormalities of hematopoietic cells or biologic abnormalities of thrombopoietin (Tpo) in the primary regulation of megakaryopoiesis. Meanwhile, reactive thrombocytosis occurs temporarily due to stimulation of megakaryopoiesis with haematological or non-haematological abnormalities. Reactive thrombocytosis is an increase in thrombopoiesis due to reactive process due to infection, chronic inflammation, malignancy, and splenectomy surgery. Bacterial or viral infections are the most common cause (about 37-78%) at any age during childhood. Reactive thrombocytosis are asymptomatic and is usually found incidentally. Based on the guidelines the British Society for Haematology recommends three initial investigations: (1) Peripheral blood smear, (2) Inflammatory markers, and (3) Iron status. Management of reactive thrombocytosis by threated the main diseases, then platelet count returns to normal after the underlying disease is resolved. The overall prognosis depends on the underlying causative condition, approximately 8% of patients with acute infection examined have mild, transient thrombocytosis and show no infectious complications. However, these patients had an increased acute-phase response, prolonged length of stay, more bacteraemia and increased mortality although it only affected a minority of patients. This distinction between essential and reactive thrombocytosis is important because it implies evaluation, prognosis and treatment.Keywords: Reactive Thrombocytosis; Secondary Thrombocytosis; Transient.